Zwischen Philosophie und Gesetz : Jüdische philosophie und theologie von 1933 bis 1938 - Meyer, Thomas, 1966- (Supplements to The journal of Jewish thought and philosophy ;, 2009)
Despite the revival of intellectual history in recent years, there is still relatively little research into German-Jewish intellectual history between 1933 and 1938. The present work studies for the first time the important discussions of the period from the debate between Leo Strauss and Julius Guttmann, Alexander Altmann's contribution to 'Jewish theology', to the reception of the work of Franz Rosenzweig and Martin Heidegger as well as the works of David Baumgardt and Fritz Heinemann. Many now forgotten texts of those discussions have been made accessible here. All the leading figures prese.